In: Computer Science
Use two different ways to prove X Y + Z = (X + Z)(Y + Z).
a) Use pure algebraic way
b) k-maps
a)
XY+Z=(X+Z)(Y+Z)
Applying distributive law to R.H.S(right hand side) then we get;
XY+Z= XY+XZ+ZY+ZZ
XY+Z= XY+XZ+ZY+Z(idempotents law , Z.Z=Z)
XY+Z=XY+Z(X+Y+1)
Applying property of 0 and 1 . that is 1+Z=1)
XY+Z=XY+Z.1
Applying property of 0 and 1, that is , Z.1=Z
so,
XY+Z=XY+Z
L.H.S=R.H.S
Hence proved
b)
Truth table of L.H.S , that is XY+Z is given below:
The k-map for the above truth table is given below:
We are finding SOP. We have obtained three groups
from group 1, we get,
001= X'Y'Z
011=X'YZ
So we get, X'Z
from group 2, we get,
001 = X'Y'Z
101= XY'Z
So we get Y'Z
from group 3, we get;
110=XYZ'
by combining all that we get L.H.S= X'Z+Y'Z+XYZ'
Truth table for the R.H.S is given below:
K-map for the truth table is given below:
we have obtained two groups
from group 1, we get ;
001= X'Y'Z
from the group 2 we get;
110=XYZ'
By combining them we get; R.H.S= X'Y'Z+XYZ'